Dimensi Motivasi Inspirasi dalam Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran di MTs Salafiyah Wonoyoso Kebumen - Fauziyah, Asnaful; Murtajib, Ahmad (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to describe the implementation of transformational leadership by the school principal, particularly in the dimension of inspirational motivation, and its impact on the quality of learning at MTs Salafiyah Wonoyoso Kebumen. Employing a qualitative approach with a phenomenological method, data were collected through interviews, observation, and documentation. The data analysis followed the Miles & Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the principal effectively applied transformational leadership by developing a clear vision grounded in Islamic values, serving as a role model, and fostering both teachers and students. The positive impacts observed include changes in teacher behavior and self-confidence, increased student motivation and discipline, as well as improved academic achievement. In conclusion, transformational leadership in the dimension of inspirational motivation significantly contributes to enhancing the quality of learning in a traditional Islamic boarding school setting.